Selective perrhenate recognition in pure water by halogen bonding and hydrogen bonding alpha-cyclodextrin based receptors. Issue 27 (20th March 2017) - Cornes, Stuart P.; Sambrook, Mark R.; Beer, Paul D.
Abstract : Alpha-cyclodextrin based anion receptors containing halogen and hydrogen bond donor motifs display selective association of perrhenate in neutral aqueous media. Abstract : Alpha-cyclodextrin based anion receptors functionalised with pendant arms containing halogen and hydrogen bond donor motifs display selective association of perrhenate in aqueous media at neutral pH. NMR and ITC anion binding investigations reveal the halogen bonding receptor to be the superior host.